2007
DOI: 10.3171/spi-07/08/184
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic ossification of the human ligamentum flavum: histopathological and immunohistochemical findings around the ossified lesion

Abstract: Object. The object of this study was to histopathologically and immunohistochemically characterize ossification of the ligamentum flavum (OLF) in samples of the thoracic spine harvested en bloc during surgery and to enhance the understanding of the ossifying process, particularly calcification and ossification. Methods. Samples of OLF plaque were obtained en bloc from 43 patients who underwent posterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
92
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 28 publications
7
92
0
Order By: Relevance
“…7,13,19,22,27 It commonly affects the lower thoracic spine, especially T9-L1. 7,15,19,20,26 This is consistent with the preoperative imaging results from our study. The exact cause of OLF has not been conclusively established.…”
Section: Discussionsupporting
confidence: 91%
“…7,13,19,22,27 It commonly affects the lower thoracic spine, especially T9-L1. 7,15,19,20,26 This is consistent with the preoperative imaging results from our study. The exact cause of OLF has not been conclusively established.…”
Section: Discussionsupporting
confidence: 91%
“…These characteristics were similar to clinical OLF. 22,28 There were puzzling features of this OLF model. None of the rats evaluated showed any gait disturbance or paralysis during the observation period, even though the spinal canal was severely encroached and the spinal cord was clearly distorted.…”
Section: Discussionmentioning
confidence: 99%
“…OLF is a well-recognized cause of spinal canal stenosis resulting in myeloradiculopathy, particularly in Asian population [2]. Previous studies have suggested that some factors, such as genetic background [3], diabetes mellitus [4], fluorosis [5], ankylosing spondylitis [6], mechanical stress [7] and regional cytokines or growth factors [8,9], were involved in the onset and progression of OLF, but the underlying pathogenesis of this disease is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%